The Oklahoma state constitution - Adkison, Danny Mark, 1950- (Oxford commentaries on the state constitutions of the United States., 2011)
"The Oklahoma State Constitution traces the historical formation and constitutional development of the state of Oklahoma. In it, Danny Adkison and Lisa McNair Palmer provide article-by-article commentary and analysis on the intent, politics, social and economic pressures, and the legal decisions that shaped and enhanced the Oklahoma constitution since it was adopted in 1907. This unparalleled commentary provides a broad understanding of state constitutional law within the context of Oklahoma's constitutional evolution. A bibliographic essay and list of cases offer significant sources for further study."--Provided by Publisher